ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PERTUMBUHAN KREDIT PADA BANK UMUM DI INDONESIA PERIODE 2011-2021 - Prabawati, Nisa Alifiyah; Susilo (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This study aims to find out how macroeconomic variable factors, namely inflation, interest rates, exchange rates and economic growth affect credit growth in Indonesia. In this study using quantitative research methods with multiple linear regression analysis. The data used in this study is in the form of secondary data in the form of a time series with a period of 44 quarters from 2011 to 2021. In this study it was found that the variables of inflation and economic growth partially have no effect on the growth of bank credit at commercial banks in Indonesia. Meanwhile, exchange rate and interest rate variables have an influence on credit growth. From the results of this study it is suggested to maintain interest rates and exchange rates through monetary policy in order to increase credit growth in Indonesia.